1984
DOI: 10.1111/j.1600-051x.1984.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical data associated with acute necrotizing ulcerative gingivitis in a dental school population*

Abstract: This study was undertaken to determine the prevalence of demographic and clinical factors of patients diagnosed as having ANUG as determined by the presence of painful, bleeding, necrotic and ulcerated interproximal gingival papillae. Results showed that ANUG patients were evenly divided between males and females relative to the general clinic population. 58% of the patients with ANUG were under 25 years of age as compared to 31% under 25 in the general clinic population. Overall, the ANUG group accounted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 18 publications
1
40
0
3
Order By: Relevance
“…The search for behavioural and psychosocial risk indicators for periodontal disease remains an important field in periodontology. Early evidence in this was obtained in studies that showed that acute necrotizing ulcerative gingivitis incidence was strongly predicted by endocrine imbalances caused by stress situations (Shannon et al 1969, Maupin & Bell 1975, Cogen et al 1983, Cohen‐Cole et al, 1983, Stevens et al 1984). In the last two decades, several investigations have been carried out on associations between psychosocial factors and periodontal illness (Marcenes & Sheiham 1992, Monteiro da Silva et al 1996, Moss et al 1996, Croucher et al 1997, Genco et al 1999, Vettore et al 2003, Solis et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The search for behavioural and psychosocial risk indicators for periodontal disease remains an important field in periodontology. Early evidence in this was obtained in studies that showed that acute necrotizing ulcerative gingivitis incidence was strongly predicted by endocrine imbalances caused by stress situations (Shannon et al 1969, Maupin & Bell 1975, Cogen et al 1983, Cohen‐Cole et al, 1983, Stevens et al 1984). In the last two decades, several investigations have been carried out on associations between psychosocial factors and periodontal illness (Marcenes & Sheiham 1992, Monteiro da Silva et al 1996, Moss et al 1996, Croucher et al 1997, Genco et al 1999, Vettore et al 2003, Solis et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Young people (15‐34 years old) in the developed world are at a higher risk of suffering from NPD, frequently in combination with other predisposing factors . Children are at a higher risk in developing countries, and this is normally associated with malnutrition and other infections .…”
Section: Necrotizing Periodontal Diseasesmentioning
confidence: 99%
“…1,3 Ateş, kırgınlık ve lenfadenopati buna eşlik edebilir. [4][5][6] Bu hastalar genellikle genç 1,6,7 ve sigara içen 6,7 bireylerdir. İmmünsüpresyon (özellikle HIV+ bireyler), 8 malnütrisyon, zayıf oral hijyen, emosyonel stres de NUG ve nekrotizan ülseratif periodontitis (NUP) gibi nekrotizan periodontal hastalıkların gelişimi için zemin hazırlar.…”
Section: Gġrġġunclassified